2009
DOI: 10.4049/jimmunol.0801755
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Lipopolysaccharide (LPS) Recognition and Signaling: Fish TLR4 Does Not Recognize LPS and Negatively Regulates NF-κB Activation

Abstract: It has long been established that lower vertebrates, most notably fish and amphibians, are resistant to the toxic effect of LPS. Furthermore, the lack of a TLR4 ortholog in some fish species and the lack of the essential costimulatory molecules for LPS activation via TLR4 (i.e., myeloid differentiation protein 2 (MD-2) and CD14) in all the fish genomes and expressed sequence tag databases available led us to hypothesize that the mechanism of LPS recognition in fish may be different from that of mammals. To she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
272
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(299 citation statements)
references
References 52 publications
16
272
3
1
Order By: Relevance
“…Both identify LPS; however, the response of bird TLR4 to LPS is much weaker than mammalian TLR4 (Keestra and van Putten, 2008). As paralogs of mammalian TLR4, fish TLR4 does not have the ability to identify LPS (Sepulcre et al, 2009); however, we have demonstrated that that grass carp TLR4s are associated with GCRV infection. This implies that the function of TLR4 varies significantly in different species.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Both identify LPS; however, the response of bird TLR4 to LPS is much weaker than mammalian TLR4 (Keestra and van Putten, 2008). As paralogs of mammalian TLR4, fish TLR4 does not have the ability to identify LPS (Sepulcre et al, 2009); however, we have demonstrated that that grass carp TLR4s are associated with GCRV infection. This implies that the function of TLR4 varies significantly in different species.…”
Section: Discussionmentioning
confidence: 65%
“…Comprehensive sequence and phylogenetic analyses have revealed that the zebrafish tlr4 genes are paralogous, rather than orthologous, to human tlr4 (Sullivan et al, 2009). A fusion protein containing the zebrafish TLR4 extracellular region and mouse TLR4 transmembrane and intracellular regions cannot identify LPS (Sullivan et al, 2009) and it has been suggested that zebrafish TLR4 recognizes unknown PAMPs (Sullivan et al, 2009;Sepulcre et al, 2009). Although most fish lost tlr4 during evolution (Oshiumi et al, 2003;Baoprasertkul et al, 2007), the structure and function study of the small number of fish which retained tlr4 may provide evolutionary clues.…”
Section: Introductionmentioning
confidence: 99%
“…Besides TLR3 fish has TLR22, a fish-specific TLR member, which can also recognize dsRNA to induce IFN through TICAM1 pathway (Matsuo et al, 2008). Study on the mechanism of LPS recognition found that fish TLR4 does not sense LPS but negatively regulated NF-kB activation (Sepulcre et al, 2009). Unlike mammalian IRF3 that is constitutively expressed in most tissues and is not modulated at the transcriptional level, trout IRF3 is markedly up-regulated by Poly I:C and rIFN (Holland et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike MyD88, no homolog of TICAM1 or TICAM2 has been identified in non-chordates such as Drosophila, Cnidaria [8], or sea urchin [10,11]. Although TICAM1 orthologs could be found in the early vertebrates lamprey [14] and zebrafish [15][16][17][18][19], they do not function in the same manner as those found in mammals. For example, human TICAM1 can induce the secretion of type I interferon by activating transcriptional factors interferon-regulatory factor (IRF) 3 and IRF7 via interaction with tumor necrosis factor receptor-associated factor 6 (TRAF6) [20], while zebrafish TICAM1, localized on the Golgi apparatus [18], induces production of zebrafish IFN in a IRF3/7-independent manner and activates NF-κB via interaction with RIP, but not with TRAF6 [17].…”
Section: Introductionmentioning
confidence: 87%
“…TICAM2 specifically acts as a bridge for TICAM1 to be successfully recruited when TLR4 recognizes LPS by coupling with CD14 and MD-2 [5,24,25]. Since endotoxin recognition by TLR4 is absent in lamprey [14], jawfish [19], and Xenopus [22], it was previously believed that the endotoxin recognition complex and the downstream signaling pathway in mammals arose after the divergence of fish and tetrapods [19]. Thus, the absence of TICAM2 in bony fish and the rapid evolution from tetrapods to mammals may have been associated with the development of the functional requirement for the formation of the endotoxin recognition complex.…”
Section: Introductionmentioning
confidence: 99%